2021
DOI: 10.1021/acs.jpcb.1c02483
|View full text |Cite
|
Sign up to set email alerts
|

Impact of Shock-Induced Cavitation Bubble Collapse on the Damage of Cell Membranes with Different Lipid Peroxidation Levels

Abstract: Although the interaction mechanism between shock waves and cells is critical for advancing the medical applications of shock waves, we still have little understanding about it. This work aims to study the response of diseased cells subjected to lipid peroxidation to the nanojet from shock wave-induced bubble collapse by using the coarse-grained molecular dynamics simulation. Factors considered in the simulations include the shock velocity (u p), movement time of piston (τp), bubble size (R), and peroxidation l… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
20
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7

Relationship

3
4

Authors

Journals

citations
Cited by 15 publications
(22 citation statements)
references
References 47 publications
2
20
0
Order By: Relevance
“…Moreover, from Table , we can see that both K A and γ L of the fully oxidized lipid bilayer (100 mol %), compared to those of the 0 mol % system, show a notable decrease. Our recent work also provided that the modulus of peroxidation bilayers was less than that of pure 1,2-dioleoyl-sn-glycero-3-phosphocholine (DOPC) bilayer. The change shows that the 100 mol % membrane model has a lower resistance to tensile loadings and damaging energy threshold.…”
Section: Resultsmentioning
confidence: 99%
“…Moreover, from Table , we can see that both K A and γ L of the fully oxidized lipid bilayer (100 mol %), compared to those of the 0 mol % system, show a notable decrease. Our recent work also provided that the modulus of peroxidation bilayers was less than that of pure 1,2-dioleoyl-sn-glycero-3-phosphocholine (DOPC) bilayer. The change shows that the 100 mol % membrane model has a lower resistance to tensile loadings and damaging energy threshold.…”
Section: Resultsmentioning
confidence: 99%
“…19,20 For membranes, more studies have focused on the effects of shock waves and bubbles due to the use of one-component models. [21][22][23] Based on multi-component models, a small number of studies have revealed the influence of components such as cholesterol 24 or peroxidized phospholipid 25 on the response of membranes to shock. In fact, typical plasma membranes (PM) contain hundreds of different lipids.…”
Section: Introductionmentioning
confidence: 99%
“…If structural damage recovers slowly, it will evolve into more severe features such as pericyte detachment, astrocyte end-feet swelling or loss, and disrupted capillary basement membrane . Therefore, we perform the recovery simulation (100 ns) with the NPzAT ensemble as before . According to the analysis of helical content and RMSD (Figure S8), only compression damage (single shockwave) can recover in 100 ns.…”
Section: Resultsmentioning
confidence: 99%
“…11 Therefore, we perform the recovery simulation (100 ns) with the NPzAT ensemble as before. 18 According to the analysis of helical content and RMSD (Figure S8), only compression damage (single shockwave) can recover in 100 ns. Protein damage subjected to shock-induced cavitation does not recover appreciably within the limited MD simulation time.…”
Section: ■ Results and Discussionmentioning
confidence: 99%
See 1 more Smart Citation